Building Public Participation in Kenya’s Devolved Government - Finch, Christopher; Omolo, Annette (World Bank Group, Washington, DC, 2015)
Kenya has embarked on a highly ambitious decentralization that seeks to fundamentally change the relationship between government and citizens under the 2010 Constitution. The Constitution and new legal framework place a strong emphasis on strengthening public participation. This paper summarizes findings and analysis from five working papers and case studies reviewing opportunities and challenges for strengthening public participation in Kenya’s newly decentralized system. It provides a consolidated list of recommendations emerging from all the working papers.